Web Design for Improving Consumer Number - Arjuna Rizaldi; T U P Jaya (Peneliti.net, 2020)
This study aims to increase consumer satisfaction in shopping activities by utilizing technological advancements as a market interface design. The research method used a qualitative descriptive method. The results of this study found out how big the impact of the interface design where the market in Indonesia can attract consumers. The market is currently growing very rapidly. Market growth is increasing throughout the world including Indonesia. Market interface design is the spearhead of competition between one market and another. The more attractive market interface design is expected to increase consumer satisfaction in shopping activities.This study aims to increase consumer satisfaction in shopping activities by utilizing technological advancements as a market interface design. The research method used a qualitative descriptive method. The results of this study found out how big the impact of the interface design where the market in Indonesia can attract consumers. The market is currently growing very rapidly. Market growth is increasing throughout the world including Indonesia. Market interface design is the spearhead of competition between one market and another. The more attractive market interface design is expected to increase consumer satisfaction in shopping activities.